Archaeolinguistics as a Way to Overcome the Impasse in Comparative Linguistics - Kozyrski, Wolodymyr Hlib; Malovichko, Alexander Victor (JOURNAL OF ADVANCES IN LINGUISTICS, 2018)
The paper exposes some essential points of our one and a half decade research results within new approach to study prehistoric stages of human language development mainly in times of ergaster-erectus domination and reflects our reaction to the protracted conceptual crisis in the comparative linguistics. As a result of fundamentally incorrectly stated goals, most of the researchers artificially limited themselves both by the defined scope of the problems to solve and by the methods used. Becoming tightly tied knot of up to now unsolved intrinsic contradictions, today comparative linguistics needs radical change. We have developed a synthetic approach that has proved its effectiveness. Our model is well aligned with prehistoric data of auxiliary historical disciplines and even IBM Genographic project. The results offer further opportunities for interesting studies.